Antiproliferative effects of ZnO, ZnO‐MTCP, and ZnO‐CuMTCP nanoparticles with safe intensity UV and X‐ray irradiation. (15th April 2015) - Sadjadpour, Susan; Safarian, Shahrokh; Zargar, Seyed Jalal; Sheibani, Nader
Abstract: In photodynamic therapy (PDT) of cancer both the light and the photosensitizing agent are normally harmless, but in combination they could result in selective tumor killing. Zinc oxide nanoparticles were synthesized and coated with the amino acid cysteine to provide an adequate arm for conjugation with porphyrin photosensitizers (meso‐tetra (4‐carboxyphenyl) porphyrin [MTCP] and CuMTCP). Porphyrin‐conjugated nanoparticles were characterized by TEM, FTIR, and UV–vis, and fluorescence spectrophotometry. The 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5‐diphenyl tetrazolium bromide (MTT) assay was used to measure cell viability in the presence or absence of porphyrin conjugates following UV and X‐ray irradiation. The uptake of the porphyrin‐conjugated ZnO nanoparticles by cells was detected using fluorescence microscopy. Our results indicated that the survival of T‐47D cells was significantly compromised in the presence of ZnO‐MTCP‐conjugated nanostructures with UV light exposure. Exhibition of cytotoxic activity of ZnO‐MTCP for human prostate cancer (Du145) cells occurred at a higher concentration, indicating the more resistant nature of these tumor cells. ZnO‐CuMTCP showed milder cytotoxic effects in human breast cancer (T‐47D) and no cytotoxic effects in Du145 with UV light exposure, consistent with its lower cytotoxic potency as well as cellular uptake. Surprisingly, none of the ZnO‐porphyrin conjugates exhibited cytotoxic effects with X‐ray irradiation, whereas ZnO alone exerted cytotoxicity. Thus, ZnO and ZnO‐porphyrin nanoparticles with UV or X‐ray irradiation may provide a suitable treatment option for various cancers.